Caudal Dexmedetomidine versus Fentanyl with Bupivacaine in Decreasing Post-Operative Pain in Pediatric Inguinoscrotal Surgery : A Comparative Study - Gyawali, Nirman P; Shrestha, Reshma; Bhattarai, Krishna P; Malla, Sadichhya Shah (Journal of Institute of Medicine Nepal, 2023)
Introduction:Despite various advancements for postoperative analgesia in children, about half of post-surgical children still experience pain. Opioids like fentanyl are used as an adjunct leading to a lower dose of caudal local anesthetics but have many side effects. Administration of caudal dexmedetomidine with local anesthetics was shown to prolong postoperative analgesia and sedation in children. This study was conducted to compare the effects of caudally administered fentanyl and dexmedetomidine in children undergoing surgery. Methods: This was a comparative clinical study in which 152 patients were included. Patients were divided into two groups to receive a caudal block, each having 76 cases. Group A and Group B received single-dose caudal analgesia using fentanyl (1mcg/kg) and dexmedetomidine (1mcg/kg) with 0.25% bupivacaine(0.75ml/kg), respectively. The analgesic effect of the caudal block was evaluated using the FLACC score and sedation using the RSS score. The statistical significance was evaluated using independent t test using confidence interval of 95% (p value<0.05). Results: The study showed no statistical significance in the demographic and operative variables between the two groups. The duration of analgesia (p value<0.001) and both the FLACC (p value 0.002) and RSS score (p value 0.004) only at 30 min postoperative values were statistically significant between the groups. The only side effect that showed statistical significance was vomiting (p value 0.03) seen in fentanyl group. Conclusion: Dexmedetomidine can thus be used safely in children along with bupivacaine in routine inguinoscrotal surgeries with additional benefits of prolonged analgesia and decreased side effects.